2018
DOI: 10.29244/jitkt.v10i2.19607
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTER MORFOMETRIK DAN ASOSIASI TUNA SIRIP KUNING Thunnus albacares DAN TUNA BAMBULO Gymnosarda unicolor (Ruppell) DI PERAIRAN SIMEULUE, PROVINSI ACEH

Abstract: Pulau Simeulue yang dikelilingi oleh terumbu tepi, secara geografis termasuk ke dalam wilayah Kabupaten Simeulue yang berbatasan langsung dengan Samudera Hindia. Tuna sirip kuning Thunnus albacares dan tuna bambulo Gymnosarda unicolor merupakan jenis epipelagik yang potensial di perairan Simeulue. Kedua jenis tuna ini belum banyak dipelajari karakter bio-ekologinya. Penelitian ini penting dilakukan untuk mengetahui karakter morfometrik dan mengkaji asosiasi spesifik tuna di perairan Simeulue. Penelitian dilaku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…The productivity of waters is determined by its limiting factors, including temperature, salinity, dissolved oxygen content, and availability of nutrients. The factors that affect the characteristics of the aquatic environment, such as salinity, temperature, and wind direction, are seasons (Burhanis et al, 2018). The producers in aquatic ecosystems are phytoplankton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The productivity of waters is determined by its limiting factors, including temperature, salinity, dissolved oxygen content, and availability of nutrients. The factors that affect the characteristics of the aquatic environment, such as salinity, temperature, and wind direction, are seasons (Burhanis et al, 2018). The producers in aquatic ecosystems are phytoplankton.…”
Section: Resultsmentioning
confidence: 99%
“…Tuna fish can be found in tropical and sub-tropical waters. Differences in longitude and latitude do not affect the spread of tuna fish (Burhanis et al, 2018). Tuna fish can be found in most Indonesian waters (Burhanis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of food resources and environmental parameters play an important role in the growth rate of gastropods (Yokoyama and Amaral, 2010). Burhanis et al (2018) reported that the topography of the waters had an effect on the distribution of the size of the type of yellowfin tuna in the waters of Simeulue. Factors of environmental conditions and genetic greatly influence changes in the morphological characteristics of both populations from Java and Bali.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted to identify the length and growth pattern of tuna gigi anjing that landed at East Simeulue's fish auction. By knowing the type and growth pattern of tuna gigi anjing, it is hoped that it can maintain stock conditions and the size distribution of the caught tuna, so that tuna gigi anjing can be managed and utilized optimally and sustainably (Burhanis et al, 2018).…”
Section: S73mentioning
confidence: 99%
“…Parameters affecting the abundance of fish in a waters are the presence or absence of the required food source, the availability of food sources related to the fertility of the waters indicated by the high content of nutrients and nutrients (Realino et al, 2007). Furthermore, Burhanis et al (2018) state that the physical limit on marine fish population is not always clear. However, the formation of a population depends on environmental (ecological) and genetic conditions that influence morphological variation.…”
Section: Growthmentioning
confidence: 99%